Characterization of maize producing households in drought prone regions of Eastern Africa - Erenstein, Olaf; Kassie, Girma T.; Langyintuo A; Mwangi W (2011)
Agriculture in eastern Africa is predominantly rainfed and maize is a major food crop, primarily produced for home consumption and the market by small-scale family farms. The study characterized farm households in the drought prone maize growing areas of eastern Africa synthesizing data from parallel household surveys in Ethiopia, Kenya, Uganda and Tanzania. The study provides a comparative analysis of the farm households’ assets, livelihood strategies and crop management practices, with an emphasis on maize and maize seed. This illustrates how farmers in a similar agro-ecological environment but with different socio-economic and institutional settings have variously adapted to living with drought and how the inherent weather risk co-determines the livelihood portfolio, agricultural intensification incentives and system development pathways. The study thereby illustrates the challenges for agricultural intensification in such drought prone environments and the scope for drought tolerant maize varieties and explores the research and development implications.